Pelaksanaan Kegiatan Rohani dan Pengembangan Kreativitas Peserta Didik dalam Konteks Pendidikan Kristen di SMTK Alor Barat Laut - Minsel Raden; Yublina Kasse (Institut Teknologi dan Bisnis Semarang, 2026)
This study aims to describe the implementation of spiritual activities and the development of student creativity at SMTK Alor Barat Laut, Alor Regency, as well as to analyze their contribution to the spiritual growth and potential development of students within the context of Christian education. Using a qualitative approach with a case study method, this research involved the principal, teachers, dormitory supervisors, and students as research subjects. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation. The results of the study show that structured spiritual activities conducted through morning worship, afternoon worship, evening worship, fasting worship, the Bible Reading Movement, memorization of golden verses, praise practice, and tambourine practice have made significant contributions to the spiritual growth and creativity development of students. The active involvement of students as worship leaders and as performers in artistic ministries fosters self-confidence, the ability to express themselves through music and the arts, as well as responsible character grounded in Christian values. Supporting factors for the implementation of these activities include a clear program structure, full support from teachers and dormitory supervisors, and the active participation of the school community, while inhibiting factors include a packed schedule and limited facilities and infrastructure. This study concludes that SMTK Alor Barat Laut has successfully realized holistic education that integrates spiritual formation and creativity development in a balanced manner, so that students grow into individuals who are faithful, creative, and character-driven in accordance with the values of Christian education.